Third Trimester Brain Growth in Preterm Infants Compared With In Utero Healthy Fetuses. Issue 3 (March 2017) - Bouyssi-Kobar, Marine; du Plessis, Adré J.; McCarter, Robert; Brossard-Racine, Marie; Murnick, Jonathan; Tinkleman, Laura; Robertson, Richard L.; Limperopoulos, Catherine
Abstract : (Abstracted from Pediatrics 2016;138:e20161640) Preterm birth is associated with lifelong neurodevelopmental disabilities even in the absence of destructive prematurity-related brain injury. The timing, progression, and functional impact of delayed brain maturation in the absence of structural brain injury remain unknown.